Associations between management practices and colostrum quality on New Zealand dairy farms. Issue 5 (3rd September 2017) - Denholm, KS; Hunnam, JC; Cuttance, EL; McDougall, S
Abstract: AIMS: To describe colostrum quality in spring-calving dairy herds in New Zealand, in terms of Brix, pH and total and coliform bacterial counts and to investigate associations between farm management practices and these measures of colostrum quality. METHODS: In June 2015, commercial dairy farms (n=105), located in North and South Islands of New Zealand, were visited shortly after the first cows had calved, and when approximately 50% and 80% of the herd had calved (early, middle and late visits). One litre of pooled colostrum that was being fed to newborn calves was collected at each visit and used to determine Brix, pH, total bacterial and coliform counts. A survey of calf management practices was conducted with the herd manager or calf rearer after the final visit. RESULTS: Of 298 pooled colostrum samples tested 29/298 (9.7%) had Brix >22%. Brix was higher on farms where calves were picked up twice daily compared with once daily (18.2 (95% CI=16.5–19.9)% vs. 15.9% (95% CI=15.2–16.6)%; p=0.012), and was lower where first milking colostrum was combined with colostrum obtained at later milkings (15.0 (95% CI=13.9–16.1)%) compared with where it was not (16.9 (95% CI=16.3–17.6)%; p=0.002). Vaccination of all cows against calf diarrhoeal pathogens was associated with increased Brix compared with no vaccination (18.1 (95% CI=16.6–19.6)% vs. 16.3 (95% CI=15.6–17.0)%; p=0.033). Mean pH of samples tested decreased from 5.97 (95% CI=5.84–6.09) to 5.58 (95% CI=5.45–5.71) for early and late-season visits, respectively (p<0.001). Of 268 samples tested, 23 (8.6%) had bacterial counts below the recommended threshold of 1.00×10 5 cfu/mL. Mean bacterial counts increased from 2.75 (95% CI=1.80–3.70)×10 8 to 4.99 (95% CI=3.95–6.03)×10 8 cfu/mL for early and late-season visits, respectively (p<0.001). Of 259 samples tested, 23 (8.9%) had coliform counts below the recommended threshold of 1.00×10 4 cfu/mL. CONCLUSIONS AND CLINICAL RELEVANCE: On a large majority of dairy farms included in this study the pooled colostrum fed to newborn calves had sub-optimal Brix and excessive bacterial counts. Farm-level risk factors such as twice daily pick up of calves from the paddocks, herd vaccination and feeding pooled colostrum that did not combine colostrum obtained at later milkings with first milking colostrum were associated with colostrum quality measures.